The effect of humour during investigative interviewing in forensic settings - Mason, Matthew (2020)
The area of investigative interviewing was revolutionised with the creation of the cognitive interview, which added psychological aspects to the basic interview conducted by the police at the time. The cognitive interview has undergone many evolutions since then, such as the enhanced cognitive interview and the PEACE interview. Humour was considered, due to its pro-social properties, such as: emotion regulation, increasing attention and engagement. This study aimed to investigate whether humour could be added to cognitive interviews, without hindering the established techniques, and potentially improving it. Using a virtual cognitive interview, participants were randomly allocated into three conditions: humorous cognitive interview (HCI), standard cognitive interview (SCI), and control standard interview (CSI). All watched the same 5-minute movie clip. The amount of correct information recalled, and total number of answers given were recorded. Results indicated that humour does not negatively affect the cognitive interview process. The implications of adding humour to cognitive interviews to assist with rapport-building and the humanitarian approach to interviewing are discussed, as well as gathering information from vulnerable populations.